Avaliação da eficiência de peneiramento e perdas de produtividade em usina de beneficiamento de calcário - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The main objective of this study, was to determine the correlation between the limestone rock moisture and the performance of the milling plant of a local limestone rock company Mario Razzera & cia LTDA. Several instrumental techniques were employed to measure and characterize the moisture content and the granule size of limestone rock before and after milling, with the aim to improve productivity yield. Samples were collected throughout the process including pre-milled rocks, sieve residue, sieved sample, and the final product. The samples were collected in days where the air humidity was high (rainy days) and low (sunny days). A granulometry assay was used to measure the limestone rock granule sizes and the Pareto chart was used to determine how many times the production was stopped to perform a maintenance on the milling machine. With the proposed methodology, we could measure the limit limestone rock moisture that do not interfere on the average productivity yield, and the acceptable percentage of fine granules that do not compromises the milling performance.
Keywords: Beneficiamento; Avaliação da produção; Umidade do calcário; Milling; Production yield; Limestone rock moisture; CNPQ::CIENCIAS EXATAS E DA TERRA